Comprehensive Non Surgical Treatment of Periodontitis Stage II grade A : A Clinical Case Report - Syifa Callista Aurellia; Patricia Virani Sekar; Veronica Septnina; Hocky B. Kasim; Ihsan Firdaus (Odonto : Dental Journal, 2025)
Introduction:  Periodontal disease is a bacterial infection of the periodontal tissue that causes inflammation, progressive loss of attachment, and bone loss. Treatment intended for halting the progression of disease, returning the dentition to a state of health and comfort both functionally and aesthetically. Aim of this case report is to present comprehensive treatment with an interdisciplinary approach. Case Report: A 22-year-old man came with chief complaints of loose lower tooth and dirty tooth, also gums bleeding easily. From the intra-oral examination was found poor oral hygiene with an OHI-S score 3.4; grade 1 tooth mobility of tooth 12, 11, 21, 22, 32, 42, grade 2 tooth 31.41; fenestration in the labial region 41; Ellis fracture grade 1 tooth 13, grade 2 tooth 12, 11, 41, grade 3 tooth 21; and gangren radix of tooth 46. The diagnosis of this case was Periodontitis stage II Grade A active condition with no risk factors. Case management includes initial therapy with scaling, root planing, tooth extraction, tooth restoration, root canal treatment, splinting and occlusal adjustment, also followed by restorative therapy with removable partial dentures. Discussion: Patients with periodontitis will always have periodontitis. The characteristics of periodontitis are irreversible, therefore treatment for periodontitis is aimed to stabilize the periodontal tissue, followed by restorative treatment as part of comprehensive treatment. Conclusion: Comprehensive non-surgical treatment for Periodontitis Stage II Grade A can restore the function and aesthetic of the tooth and mouth.